2010
DOI: 10.1021/bi101397u
|View full text |Cite
|
Sign up to set email alerts
|

The Neutral Lipid Composition Present in the Digestive Vacuole of Plasmodium falciparum Concentrates Heme and Mediates β-Hematin Formation with an Unusually Low Activation Energy

Abstract: In eukaryotic cells, neutral lipids serve as major energy storage molecules; however, in Plasmodium falciparum, a parasite responsible for causing malaria in humans, neutral lipids may have other functions during the intraerythrocytic stage of the parasite life cycle. Specifically, experimental data suggest that neutral lipid structures behave as a catalyst for the crystallization of hemozoin, a detoxification byproduct of several blood-feeding organisms, including malaria parasites. Synthetic neutral lipid dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
79
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 52 publications
(111 reference statements)
8
79
0
Order By: Relevance
“…Hemozoin crystals have been observed immersed in the lipid nanospheres (9,16), or with their basal surfaces attached to the DV membrane (18)(19)(20) and other crystal faces apparently exposed to the aqueous subphase. Whereas it has been hypothesized that hemozoin crystals nucleate on the DV membrane (17,20), the debate on the medium, aqueous or organic, from which soluble hematin reaches the crystals and associates to them has yet to be reconciled (18)(19)(20)(31)(32)(33).…”
Section: Resultsmentioning
confidence: 99%
“…Hemozoin crystals have been observed immersed in the lipid nanospheres (9,16), or with their basal surfaces attached to the DV membrane (18)(19)(20) and other crystal faces apparently exposed to the aqueous subphase. Whereas it has been hypothesized that hemozoin crystals nucleate on the DV membrane (17,20), the debate on the medium, aqueous or organic, from which soluble hematin reaches the crystals and associates to them has yet to be reconciled (18)(19)(20)(31)(32)(33).…”
Section: Resultsmentioning
confidence: 99%
“…Neutral lipids are required to support membrane biogenesis, and are also known to play a role in the phenomenon of haemozoin formation in the malaria parasite's DV 30 . ABCG2, in mammals, protects against toxic levels of the haeme precursor protoporphyrin IX (ref.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo formation of hemozoin is likely mediated by neutral lipid particles located in the acidic digestive vacuole of the parasite (pH 4.9), where hemoglobin digestion occurs (4,23). Indeed, a recent study demonstrated that these lipids are kinetically sufficient mediators of ␤-hematin formation and could account for the detoxification of free heme in vivo (13). Unfortunately, the relatively high cost associated with neutral lipids and the requirement to prepare fresh mediator before each screen limits their use in HTS.…”
Section: Discussionmentioning
confidence: 99%
“…This solubilization of free heme has been shown to be the rate-limiting step in this reaction. It is doubtful that the in vivo process of hemozoin formation occurs through a similar mechanism of solubilization (6,13). In the NP-40 detergent assay, however, the detergent micelles more accurately mimic the neutral lipid particles present within the native environment of the parasite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation